2021
DOI: 10.3390/cancers13081768
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of the Transcriptome Profiles and Co-Expression Networks of Tumour Endothelial Cells Identifies Several Tumour-Associated Modules and Potential Therapeutic Targets in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the sixth most common cancer and the third most common cause of cancer-related death, with tumour associated liver endothelial cells being thought to be major drivers in HCC progression. This study aims to compare the gene expression profiles of tumour endothelial cells from the liver with endothelial cells from non-tumour liver tissue, to identify perturbed biologic functions, co-expression modules, and potentially drugable hub genes that could give rise to novel therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…It is well documented that the difference in gene expression between TECs and NECs 3,17,54 may be due to the different origins and high mutagenicity of TECs. However, only a few studies have shown that the changes of biological functions of endothelial cells are caused by overexpression or low expression of differential genes in TECs.…”
Section: Differences Between Tumour Endothelial Cells and Normal Endo...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is well documented that the difference in gene expression between TECs and NECs 3,17,54 may be due to the different origins and high mutagenicity of TECs. However, only a few studies have shown that the changes of biological functions of endothelial cells are caused by overexpression or low expression of differential genes in TECs.…”
Section: Differences Between Tumour Endothelial Cells and Normal Endo...mentioning
confidence: 99%
“…It may be that endothelial cells (ECs) are embedded in the vascular wall, which is difficult to separate, and the number of cells is small, so it is necessary to evaluate the gene expression profile of fewer cells 17 . Genome variation analysis shows the gene expression profile of TECs, providing a framework for gene analysis of TECs in the future 54 . With the application of scRNA‐seq technology, the transcriptome of TECs has gradually been elucidated 61 .…”
Section: Differences Between Tumour Endothelial Cells and Normal Endo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression data of Meso-CAFs was compared to CAF-3 and to data of 31 PM cell lines available from a previous publication [10]. Analysis and comparison of expression data was conducted in R [13], and differentially expressed genes between cell types (Meso-CAF, CAF-3, PM) were determined using "limma" package [14] as previously described by Mohr et al [15]. Genes with multiple oligonucleotide probes on the array were summarized to the probe with maximal interquartile range using the package "gene lter" [16].…”
Section: Whole Genome Gene Expression Microarraysmentioning
confidence: 99%
“…The European COST (Cooperation in Science and Technology) Action STRATAGEM “New Diagnostic and Therapeutic Tools against Multidrug-Resistant Tumors” was initiated in April 2018, as a multidisciplinary open consortium studying the diagnostic, therapeutic and toxicological challenges associated with MDR tumors. Indeed, multiple tools must be used to overcome MDR, including molecular modelling [ 12 ], high-throughput bioinformatic analyses [ 9 , 13 ], biochemical and pharmacological assays together with advanced technological tools [ 14 ], rational design and synthesis of new synthetic or natural bioactive compounds [ 10 , 15 , 16 ] and preparation of formulations using nanocarriers to improve drug solubilization, selectivity and anti-cancer action [ 11 ].…”
mentioning
confidence: 99%